A new species of Lejeunea Lib. (Lejeuneaceae) from Brazilian Savanna - Pinheiro, Ana Vera T.; Peralta, Denilson F. (Phytotaxa, 2025)
Lejeuneaceae Rostovzev is the largest family among liverworts, comprising a tropical and subtropical group of leafy species with considerable morphological diversity. These species can be found on a wide range of substrates and across all Phytogeographic Domains in Brazil. Among the representatives of this family, Lejeunea Libert. is the most diverse genus, with a Neotropical, Paleotropical, and Holarctic distribution. As part of a floristic survey of bryophytes conducted in the Chapada dos Guimarães National Park, in the state of Mato Grosso, Brazil, a species with unique characteristics was found and is here described as a new to Science. Identification was carried out using a stereomicroscope and light microscope, considering gametophytic characters, particularly the underleaf and lobule shape, the apex and margins of the leaf lobes, the cell shape, and stem cross-section. Therefore, Lejeunea tridenticulata A.V.Tourinho P. & D.F.Peralta, sp. nov., is known only from a single specimen collected in the Central-West region of Brazil, in the state of Mato Grosso, in plateau areas, within the gallery forest vegetation of the Cerrado Phytogeographic Domain, at an altitude of 513 meters. It was found associated with eight other bryophyte species, growing on twigs. This species is mainly distinguished by its underleaves, which are bifid to trifid with markedly toothed margins bearing 1 to 4 teeth—features not found in any other species of the family or genus. This highlights the importance of floristic surveys for advancing our knowledge of biodiversity.